2015
DOI: 10.3923/ajbkr.2015.60.70
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Impeller Number and Position on Growth Yield and Virulence of Bordetella pertussis Strain 509 During Large Scale Batch Fermentor Cultivation

Abstract: Studies have been undertaken to investigate, the effect of impeller number and its position upon the growth yield of Bordetella pertussis strain 509 during large scale batch cultivation. It was shown that, the maximum growth yield opacity was found to be 70 IOU mLG 1 at 48 h cultivation in single impeller fixed at the bottom position of fermentor vessel. Whereas the optimal and moderate culture opacity 60 and 50 IOU mLG 1 was observed during the two impellers mounted at two different positions on the shaft. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This may be due to differences in the bioreactor design, such as in the impeller spacing, baffle and sparger specifications, and vessel ratio, which helped to provide better yeast growth and IAA production in the 15-L bioreactor than in the 2-L bioreactor. In 2015, Shivanandappa, et al 56 reported that impeller position affected the growth yield of Bordetella pertussis strain 509 during large-scale batch fermentation. A single impeller was found to improve the growth yield of B. pertussis strain 509, whereas two and three impellers located at various positions resulted in a decrease in the growth rate due to the disturbance of vortex flows and broth mixing resulting in less dissolved oxygen being transferred.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to differences in the bioreactor design, such as in the impeller spacing, baffle and sparger specifications, and vessel ratio, which helped to provide better yeast growth and IAA production in the 15-L bioreactor than in the 2-L bioreactor. In 2015, Shivanandappa, et al 56 reported that impeller position affected the growth yield of Bordetella pertussis strain 509 during large-scale batch fermentation. A single impeller was found to improve the growth yield of B. pertussis strain 509, whereas two and three impellers located at various positions resulted in a decrease in the growth rate due to the disturbance of vortex flows and broth mixing resulting in less dissolved oxygen being transferred.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to differences in the bioreactor design, such as in the impeller spacing, ba e and sparger speci cations, and vessel ratio, which helped to provide better yeast growth and IAA production in the 15-L bioreactor than in the 2-L bioreactor. In 2015, Shivanandappa, et al 52 reported that impeller position affected the growth yield of Bordetella pertussis strain 509 during largescale batch fermentation. A single impeller was found to improve the growth yield of B. pertussis strain 509, whereas two and three impellers located at various positions resulted in a decrease in the growth rate due to the disturbance of vortex ows and broth mixing resulting in less dissolved oxygen being transferred.…”
Section: Discussionmentioning
confidence: 99%